Upaya Kepolisian Dalam Menanggulangi Kasus Pencabulan Yang Dilakukan Orang Tua Terhadap Anak Di Wilayah Polres Gorontalo - Siti Nurhalisa Lahamutu; Moh R U Puluhulawa; Mohamad Taufiq Zulfikar Sarson (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This journal discusses the police's efforts to tackle cases of sexual abuse committed by parents against children in the Gorontalo Police area. Through a case analysis approach, this research explores the forms of police countermeasures at the Gorontalo Resort Police, such as pre-emptive countermeasures are initial efforts made by the police to prevent the occurrence of crime so it is usually called initial prevention, and preventive countermeasures are is a follow-up to pre-emptive efforts which aim to prevent, reduce and eliminate crime, namely by avoiding clothing that can cause sexual stimulation of the opposite sex, as well as repressive countermeasures are efforts carried out by the authorities after a crime occurs, such as taking action against the perpetrators accordingly. with his actions. Such as strict law enforcement, fair trials, rehabilitation